Clinical significance of novel biomarkers to predict the natural course of hepatitis B infection - Wu, Weikang; Yuan, Xiaojie; Zhang, Weilu; Zhou, Haowei; Kong, Xiangyu; He, Zhen; Fu, Ting; Zhang, Wenhua; Jia, Wenling; Liang, Chunhui; Tang, Haitao; Wang, Fengmei; et al. (Frontiers in Public Health, 2022)
Abstract Background and Aim: Chronic hepatitis B (CHB) can be divided into immune tolerance (IT), immune clearance (IC), hepatitis B e antigen (HBeAg)-negative inactive/quiescent carrier (ENQ), and HBeAg-negative hepatitis (ENH) phases. The conventional biomarkers used to distinguish these phases have limitations. We examined the clinical significance of hepatitis B virus (HBV) RNA and hepatitis B core-related antigen (HBcrAg) as novel biomarkers. Methods: One hundred eighty-nine treatment-naïve patients were categorized by CHB phase (IT = 46, IC = 45, ENQ = 49, ENH = 49). The associations of HBV RNA and HBcrAg with HBV DNA and alanine transaminase (ALT) were analyzed. The decision tree model was used to distinguish the four phases in the natural course of CHB. Results: The concentrations of HBV RNA and HBcrAg were highest in the IT and IC phases (P < 0.01). Serum HBV RNA was similar to HBcrAg in treatment-naïve patients. HBV RNA and HBcrAg correlated with HBV DNA in the HBeAg+ and HBeAg− status (HBV RNA: e+ r = 0.51, e− r = 0.62; HBcrAg: e+ r = 0.51, e− r = 0.71), but their association with HBV DNA differed among phases. The accuracy, sensitivity, and specificity of HBcrAg with ALT in distinguishing the CHB phases were 95.65%, 95.83%, and 95.55%, respectively. Conclusion: Serum HBV RNA and HBcrAg may be useful to monitor CHB progression.